Pelatihan Adab Makan Dan Minum Sesuai Ajaran Islam di SD Banggai, Sulawesi Tengah - Kusno Setiadi; Anik Mufarrihah; Hasna Koba’a; Tomi Bidjai; Erniwati Laabute; Kalsum Hamid; Magfira Ningsi (Universitas Darunnajah, Jakarta, Indonesia, 2024)
Adab training in eating and drinking is an attempt to provide character education for students. The material for eating and drinking is given according to Islamic teachings. This training aims to teach students about eating and drinking in accordance with the true teachings of Islam. SD N Tintingan is the location of this service activity in February 2024. The form of service activities is in the form of training on eating and drinking through the stages of surveys and coordination with partners, making training designs and training presentations. The results of this service showed that there was an increase in participants' understanding of eating and drinking according to Islamic teachings. Participants felt very understanding of eating and drinking according to the true teachings of Islam. Participants of the next activity can apply these rules in their daily lives both in the school environment and at home.